2022
DOI: 10.15517/rev.biol.trop..v70i1.49798
|View full text |Cite
|
Sign up to set email alerts
|

Mecanismos inmunológicos en Cnidaria: un sistema inmune basal de gran complejidad e interés bioprospectivo

Abstract: Introducción: La protección ante agentes biológicos propios y externos de los cnidarios dependen de la inmunidad innata, la cual consta de tres procesos inmunológicos principales: 1) reconocimiento inmunológico, 2) señalización intracelular, y 3) respuesta efectora. Objetivo: revisar críticamente el conocimiento actual del repertorio molecular involucrado en la respuesta inmune en cnidarios, así como, su papel en el establecimiento de la simbiosis, y las posibles aplicaciones biotecnológicas de las moléculas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
0
2
0
2
Order By: Relevance
“…Ramachandran plots allowed visualized both amino acids present in energetically favored regions for dihedral angles, as well as amino acids in questionable regions for each of the 3D models (Supplementary Figure 1). The structure that presented the largest number of amino acids (Leal et al, 2022) with dihedral angles "not allowed" was that of peptide 8A described in the species Discosoma sp. On the other hand, the 5P peptide described in Goniastrea aspera showed that all its amino acids have dihedral angle conformations for forming a-helix and b-sheet structures.…”
Section: Amp's Models Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ramachandran plots allowed visualized both amino acids present in energetically favored regions for dihedral angles, as well as amino acids in questionable regions for each of the 3D models (Supplementary Figure 1). The structure that presented the largest number of amino acids (Leal et al, 2022) with dihedral angles "not allowed" was that of peptide 8A described in the species Discosoma sp. On the other hand, the 5P peptide described in Goniastrea aspera showed that all its amino acids have dihedral angle conformations for forming a-helix and b-sheet structures.…”
Section: Amp's Models Qualitymentioning
confidence: 99%
“…The genomes of Cnidarians have a great complexity that is reflected in the repertoire of innate immune genes. Several researches have allowed the description of a variety of molecules involved in the immunological processes of innate immunity (Leal et al, 2022). One of these processes is immunological recognition, in which molecular patterns in a pathogen are recognized to induce a response that leads to its destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Las pruebas de alergia y las evaluaciones inmunológicas pueden ser útiles para identificar la causa y el mecanismo de las reacciones. Además, es importante tener un historial detallado de los medicamentos utilizados previamente y de cualquier reacción adversa relacionada (Leal et al, 2022).…”
Section: Mecanismos Inmunológicosunclassified
“…Leal et al (2022), los mecanismos inmunológicos desempeñan un papel crucial en las reacciones adversas medicamentosas, especialmente en las reacciones de hipersensibilidad o alergias a los medicamentos. Estas reacciones se producen cuando el sistema inmunológico del cuerpo reconoce erróneamente un medicamento como una sustancia extraña y desencadena una respuesta inmunológica exagerada.Existen diferentes tipos de reacciones de hipersensibilidad mediadas porel sistema inmunológico, y se clasifican en cuatro tipos principales: tipo I, tipo II, tipo III y tipo IV.…”
unclassified